Influence of thermal input on microstructure and wear properties of surface alloyed DSS with SiC by TIG melting techniques - Paijan, Lailatul Harina; Mamat, Mohd Fauzi; Abu Bakar, Mohd Hadzley; Abd Aziz, Mohd Syafiq (Microscopy Society of Malaysia, 2024)
In arc TIG torch welding, thermal input is important because it affects the thermal efficiency and quality of the welded materials. A change in the microstructure with the deposition of ceramic particles can have a direct effect on the improvement of wear properties of a surface alloying using various thermal input of TIG torch welding. This work is required due to the limitation of AISI Duplex-2205 which has weaknesses in wear properties during application. In this work, this material was surface alloyed with addition of SiC ceramic powder with particle size of 100 µm and melted using different thermal input of TIG torch melting heat source to improve the microstructure and wear properties. Microstructural analysis, micro-hardness and wear properties were conducted on this material at different thermal input conditions. The obtained microstructural examination was correlated with corresponding hardness and wear properties, which were determined from morphological, hardness value on the top surface and wear rate evaluation. The highest hardness with value of 1600 Hv and wear rate with value of 2.3 x 10-4 mm3/Nm was obtained in the sample fabricated under thermal input of 0.768 KJ/mm. The microstructural changes observed on the surface alloyed DSS with the formation of dendrites microstructures due to re-solidification between AISI Duplex-2205 and SiC ceramic particles which indicated the good hardness properties against wear degradation in tribological applications.